Sleep quality in patients with chronic spontaneous urticaria - Fatma Etgü; Sevda Önder (Turkderm Turkish Archives of Dermatology and Venereology, 2023)
Background and Design: Chronic urticaria is characterized by the occurrence of hives (wheals) and/or angioedema for 6 weeks or more. Materials and Methods: This was a cross-sectional study. All participants were asked to complete the Epworth Sleepiness Scale (ESS), Pittsburgh Sleep Quality Index (PSQI), and Insomnia Severity Index (ISI). Patients with chronic spontaneous urticaria (CSU) completed the Urticaria Activity Score 7 (UAS-7) and Chronic Urticaria Quality of Life Questionnaire. Results: The study included 88 patients with CSU (26 men and 62 women) and 88 healthy controls (26 men and 62 women). The mean global PSQI score was 7.27+-4.54 in the patient group and 4.97+-2.82 in the control group (p<0.001). The mean ISI score was significantly higher in the patient group than in the control group (p=0.001). The mean ESS score did not differ between the patient and control groups (p=0.262). Conclusion: In this study, we found that more people in the patient group experienced poor sleep quality and insomnia compared with the control group. In the patient group, female sex, presence of CSU for more than 5 years, and presence of angioedema were associated with poor sleep quality. Patients with severe disease (high UAS-7 scores) had worse sleep quality. The erythrocyte sedimentation rate was found to be correlated with sleep disturbance.